The role of spirituality and resilience among Yemeni refugee students in the Kingdom of Saudi Arabia - Manal Ali Ahmed Garoon; Shahabuddin Hashim; Nik Rosila Nik Yaacob (Institute of Advanced Engineering and Science, 2022)
The purpose of this article was to explore the role of spirituality and resilience in coping and adaptation among Yemeni refugee students. This qualitative study aimed to explore the themes of spirituality and resilience that emerged among Yemeni refugee students who have experienced from conditions of war after the war that began in Yemen in 2015. This study applied in-depth, semi-structured interviews to explore the themes through qualitative interviews with Yemeni refugee students in Saudi Arabia. Thematic analysis was used to determine the role of spirituality and resilience in coping and adaptation. The study showed that Yemeni refugee students commonly use five main coping and adaptation methods to improve their lives in the host country.